Evaluating Game-Based Learning using WOW Crossword Application through Students' Feedback - Prihatini, Fajar; Sumartono, Sumartono; Septiani, Novia Dwi (Sekolah Tinggi Agama Islam Al-Furqan, Makassar - Indonesia, 2025)
The purpose of this study is to evaluate the WOW Crossword application as a part of Game-Based Learning in teaching vocabulary through students’ feedback. This study is a descriptive quantitative approach. The subject of the research is the students at SMK N 1 Warureja. There were 36 students majoring in X AKL.3. The data was gained from students’ feedback consisted of 15 statements, which were categorized into 4 rating scales in the level of Very Poor (1), Poor (2), Good (3), and Very Good (4). The feedback form will then be analysed and tabulated to determine the students’ Feedback performance, vocabulary achievement of the students, and students’ Feedback interpretation criteria in each meeting. The average feedback scores started at 51.5 to 60, which indicates that a significant majority of the students expressed high levels of satisfaction, motivation, and enjoyment during the learning process. Furthermore, feedback scores showed relatively low standard deviations, such as 3.2 in Meeting 5 and 4.3 in Meeting 4. The study also examined the development of students’ vocabulary acquisition at each of the meetings. The average vocabulary scores ranged from 13.78 to 22.67, reflecting the increasing familiarity of students with both the content and the game mechanism, as well as more targeted or appropriately challenging vocabulary tasks in those sessions. The minimum total score obtained by a student was 1854, while the maximum was 2044, out of a possible maximum value of 2160, which was then categorized into Good to Very Good. The Students consistently provided high feedback scores across all meetings, indicating strong motivation, enjoyment, and satisfaction with the learning method. These results confirm the potential of game-based tools to create an interactive and stimulating classroom atmosphere.